Effect of Silver Nanoparticles on Microleakage and cytotoxicity of New Universal Adhesive - Fatemeh Koohpeima; Mohammad Javad Mokhtari; Amir Hossein Rezaie (Mashhad University of Medical Sciences, 2022)
Introduction: Despite the incredible popularity of dental composites, their application is associated with several difficulties, one of the most important of which is the microleakage phenomenon. Incorporation of silver nanoparticles in composites exerts antibacterial effects; nonetheless, the impact of silver nanoparticles on microleakage has not yet been studied. This research conducted to assess the effect of silver nanoparticles application as a precursor on the microleakage of composite-filled clV cavities using two different approaches of universal bond application. Methods: Sixty non-carious human molars were collected, and clV cavities were provided on the buccal surfaces. The samples were categorized to 4 groups (n=15 in each group) and were restored using four different methods. After placement in 2% basic fuchsin solution for 24 h, permeability was determined between the cavity wall and restorative material in the gingival and occlusal margins. Thereafter, one sample of each group was selected. After preparation, the specimens were analyzed using backscattered electron scanning electron microscopy. Finally, the cytotoxicity was assessed by the Methyl-thiazolyl-tetrazolium (MTT) assay. Results: In both gingival and occlusal margins, if the silver nanoparticles were used, microleakage significantly decreased (P≤0.001). The addition of silver nanoparticles had no adverse effect on human gingival fibroblasts (HGF) cell viability. Conclusion: It seems that the use of silver nanoparticles in the total-etch method can improve phosphoric acid penetration into dentinal tubules, increases the depth of etching, and promotes the bond quality